Electrical and magnetic properties of sm doped La 2/3 Ca 1/3 Mn03 / Z. Gebrel … [et al.] - Gebrel, Z.; Halim, S. A.; Chik, Abdullah; Hamadneh, Imad; Lim, K. P.; W. Yusoff, W. M. Daud (2002)
The effect of the substitution of Sm in the colossal magnetoresistance (CMR), La O.67Ca0.33MnO3 ceramics has been studied. A series of x = .0,0.01,0.02,0.03,0.04 and 0.1 of (La1-x Smx)2/3 MnO3 were prepared using a solid state reaction method. The magnetic and electrical properties have been investigated by a.c. magnetic susceptibility and DC electrical resistance measurement. The metal to insulator temperature Tp shifted to lower temperature as Sm doping increases, which indicates the loss of ferromagnetic order. The Curie temperature, Tc of each samples also shifted towards lower temperature as the Sm content increases. For samples with x = 0.03 and x = 0.1 the ac susceptibility display sharp peak suggesting a spin glass behaviour.